Symbolic Meaning of Drama âPerlawanan Diponegoroâ - Sahid, Nur; Susantina, Sukatmi; Septiawan, Nicko (Harmonia: Journal of Arts Research and Education, 2016)
Study on Drama entitled âPerlawanan Diponegoroâ or âDiponegoro Insurrectionâ by Lephen Purwanto is aiming at deeply digging the semiotic meanings attached to it. This study employed Keir Elamâs theatrical semiotics as the approach, while Krippendorfâs content analysis was implemented as the method of study. Citing from Krippendorf, content analysis is a method that is particularly develop to study symbolical phenomena with a major purpose that is to dig and reveal other examined phenomena, comprising content, meaning, and essential element of a literary work.